EFFECT OF HEAT STRESS ON THERMOREGULATORY, LIVE BODYWEIGHT AND PHYSIOLOGICAL RESPONSES OF DWARF GOATS IN SOUTHERN NIGERIA - Okoruwa, M.I. (European Scientific Journal, ESJ, 2014)
The study was conducted to investigate the effect of heat stress on thermoregulatory, live bodyweight and physiological responses of dwarf goats in southern Nigeria. Twenty-four West African dwarf goats, aged between 8 and 9 months with average bodyweight of 8.00+0.53kg were used for the study. The goats were assigned to three (T1, T2 & T3) treatment groups in a completely randomized design with eight goats per treatment group. T1 goats were confined in their pens throughout the study. T2 goats were opened from their pens to the open yard between 8.00am and 1.00 pm daily, while T3 goats were opened from their pens to open yard between 1.00pm and 6.00pm daily. The results obtained showed that morning time was significantly (P<0.05) highest in relative humidity (62.51%), while afternoon time was highest (P<0.05) in ambient temperature (33.010C) and temperature-humidity index (83.97). Final and change in live bodyweight (8.66 and 0.04kg), white blood cell (12.60Ã—109 L) and serum calcium (12.66mmol L) were significantly (P<0.05) best in T1 compared to T2 and T3. Rectal and skin temperature (41.02 and 40.680C), respiratory rate (23.01 breaths/min), pulse rate (91.04 beats/min), packed cell volume (32.34%), haemoglobin (9.09g/dl), red blood cell (10.37 Ã—1012 L), total protein (5.12g/dl), albumin (3.88g/dl), albumin and globulin ratio (3.13%), glucose (71.01mg/dl), sodium (104.35mmol/L) and potassium (6.22mmol/L) were significantly highest in T3. No significant (P>0.05) different was observed in initial live bodyweight and serum globulin. It is concluded that heat stress had significant effect on thermoregulatory, live bodyweight and physiological responses of dwarf goats in southern Nigeria.